Costs of hospitalization with respiratory syncytial virus illness among children aged < 5 years and the financial impact on households in Bangladesh, 2010 - Bhuiyan, Mejbah Uddin; Luby, Stephen P.; Alamgir, Nadia Ishrat; Homaira, Nusrat; Sturm-Ramirez, Katharine M.; Gurley, Emily Suzane; Abedin, Jaynal; Zaman, Rashid Uz; Alamgir, Asm S.M.; Rahman, Mahmudur M.Atiqur; Ortega-Sánchez, Ismael R.; Azziz-Baumgartner, Eduardo (© 2017 University of Edinburgh, 2018)
This article was published in the Journal of Global Health [© 2017 University of Edinburgh] The Journal's website is at: https://www.ncbi.nlm.nih.gov/pubmed/28702175